The secret language of sisters - Rice, Luanne (Point, an imprint of Scholastic Inc., 2016)
Mathilda (Tilly), fourteen, and Ruth Anne (Roo), sixteen, are sisters and best friends in Connecticut, but when Roo crashes her car while texting she is confined to a hospital bed with "locked-in syndrome," aware of her surroundings, but apparently comatose--and Tilly must find a way to communicate with her sister, while dealing with her own sense of guilt.